Disregarding the Constitutional Court Decision Concerning the Prohibition of Concurrent Deputy Minister Positions: Pengabaian Putusan Mahkamah Konstitusi Terkait Larangan Rangkap Jabatan Wakil Menteri - Sari, Sonia Sekar; Ilmar, Aminuddin; Djafar, Eka Merdekawati; Faiz, Pan Mohamad (Jurnal Konstitusi, 2023)
The presence of the deputy minister position in the Indonesian government system has been a constitutional issue, both in its appointment and the issue of the prohibition of holding multiple positions. This article discusses Constitutional Court Decision Number 80/PUU-XVII/2019, which provides clarity on the constitutionality of the appointment of deputy ministers and the prohibition of holding multiple positions, including as commissioners or directors in state-owned or private companies. Despite this decision, the analysis indicates that the prohibition of holding multiple positions for deputy ministers is still disregarded, as some deputy ministers currently serve as Commissioners in State-Owned Enterprises (SOEs). This research uses a normative approach by analyzing secondary data. The result is that the Constitution is ignored because the Constitutional Court Decision regarding the prohibition of holding multiple positions for deputy ministers is not implemented. To address this non-compliance, if deputy ministers continue to hold positions as commissioners, the President should be able to dismiss them based on the State Ministry Law and Constitutional Court Decision, and impose sanctions in the form of an obligation to compensate the state’s financial loss incurred during the concurrent positions.